Wireless measurement for passive pressure sensors in high temperature environment. Issue 2 (16th March 2015) - Hong, Yingping; Liang, Ting; Jia, Pinggang; Liu, Wenyi; Tan, Qiulin; Li, Chen; Zheng, Tingli; Ge, Binger; Xiong, Jijun
Abstract : Purpose: – Physical contact and traditional sensitive structure Physical contact and traditional pressure-sensitive structures typically do not operate well in harsh environments. This paper proposes a high-temperature pressure measurement system for wireless passive pressure sensors on the basis of inductively coupled LC resonant circuits. Design/methodology/approach: – This paper begins with a general introduction to the high-temperature pressure measurement system, which consists of a reader antenna inductively coupled to the sensor circuit, a readout unit and a heat insulation unit. The design and fabrication of the proposed measurement system are then described in detail. Findings: – A wireless passive pressure sensor without an air channel is fabricated using high-temperature co-fired ceramics (HTCC) technology and its signal is measured by the designed measurement system. The designed heat insulation unit keeps the reader antenna in a safe environment of 159.5°C when the passive sensor is located in a 900°C high-temperature zone continuously for 0.5 h. The proposed system can effectively detect the sensor's resonance frequency variation in a high bandwidth from 1 to 100 MHz with a frequency resolution of 0.006 MHz, tested from room temperature to 500°C for 30 min. Originality/value: – Expensive and bulky equipment (impedance analyzers or network analyzers) restrict the use of the readout method outside the laboratory environment. This paper shows that a novel readout circuit can replace the laboratory equipment to demodulate the measured pressure by extracting the various sensors' resonant frequency. The proposed measurement system realizes automatic and continuous pressure monitoring in a high-temperature environment with a coupled distance of 2.5 cm. The research finding is meaningful for the measurement of passive pressure sensors under a wide temperature range.